2010
DOI: 10.1007/s10514-010-9183-2
|View full text |Cite
|
Sign up to set email alerts
|

Unmanned aerial vehicles UAVs attitude, height, motion estimation and control using visual systems

Abstract: This paper presents an implementation of an aircraft pose and motion estimator using visual systems as the principal sensor for controlling an Unmanned Aerial Vehicle (UAV) or as a redundant system for an Inertial Measure Unit (IMU) and gyros sensors. First, we explore the applications of the unified theory for central catadioptric cameras for attitude and heading estimation, explaining how the skyline is projected on the catadioptric image and how it is segmented and used to calculate the UAV's attitude. Then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…A non-symmetric membership function is defined by non-equal sizes for the fuzzy sets of this variable. It has been proved in [18], [19], [20] that a special definition of the quantity and size of the fuzzy sets in the different variables can improve the behavior of a Fuzzy controller.…”
Section: Mofs: a Fuzzy Control Design Softwarementioning
confidence: 99%
“…A non-symmetric membership function is defined by non-equal sizes for the fuzzy sets of this variable. It has been proved in [18], [19], [20] that a special definition of the quantity and size of the fuzzy sets in the different variables can improve the behavior of a Fuzzy controller.…”
Section: Mofs: a Fuzzy Control Design Softwarementioning
confidence: 99%
“…With this software, it is possible to easily define a fuzzy controller with the required number of inputs and to select the type of membership functions, the defuzzification model and the inference operator. A more detailed explanation of this software can be found in [15]. The controller has two inputs and one output.…”
Section: Fuzzy Controllermentioning
confidence: 99%
“…Anytime the weight of a rule becomes negative the system sets the output of the rule to the one given by the human driver. Further details of the software are given at [15]. Table 1 shows the base of rules which enclose the knowledge of the controller.…”
Section: Fuzzy Controllermentioning
confidence: 99%
“…Prior work demonstrating visual-based tracking has shown the potential of solely visual based tracking [16] (this algorithm operates on a restricted number of pixels from a frame at 10fps) and pose estimation [17] (designed to operate at 15fps). Related visual based UAV cueing has shown that visual odometry has been achieved at 25fps on a two-camera setup with a 1.5GHz Core 2 Duo processor [18].…”
Section: Introductionmentioning
confidence: 99%